2019
DOI: 10.1016/j.heliyon.2019.e02982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching and variety on the physico-chemical, functional and rheological properties of three new Irish potatoes (Cipira, Pamela and Dosa) flours grown in the locality of Dschang (West region of Cameroon)

Abstract: Enzymatic browning, which usually occurs during irish potato tuber processing, causes deterioration in the nutritional, functional, physical and acceptability quality of the products derived from this matrix. To fight against this phenomenon, several treatment methods have been developed, such as bleaching. This led us to investigate the effect of bleaching on the physico-chemical, functional and rheological properties of three irish potato varieties. To achieve our objective, blanched and unbleached irish pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
(62 reference statements)
4
8
1
4
Order By: Relevance
“…Klang et al. (2019) studied the reducing sugar content of different varieties of potatoes, and the results showed that the reducing sugar content of different varieties of potatoes was about 0.40% to 2.54%, which is basically consistent with the reducing sugar content of the control group in this experiment. Potatoes are rich in protein, which accounts for about 3% to 6% of dry weight, and studies have shown that the protein of potato is better than that of most plants and grains (Zeng et al.,2013).…”
Section: Resultssupporting
confidence: 82%
“…Klang et al. (2019) studied the reducing sugar content of different varieties of potatoes, and the results showed that the reducing sugar content of different varieties of potatoes was about 0.40% to 2.54%, which is basically consistent with the reducing sugar content of the control group in this experiment. Potatoes are rich in protein, which accounts for about 3% to 6% of dry weight, and studies have shown that the protein of potato is better than that of most plants and grains (Zeng et al.,2013).…”
Section: Resultssupporting
confidence: 82%
“…In temperature 60°C and the soaking hydrogen-rich water, the bonds stabilizing the semi-crystalline structure of the starch break and replaced by water molecules, causing the granules to swell. The high-value swelling power related to high pH (Klang, et al, 2019). Swelling power potato flour modified was higher than control (4.2 g/g).…”
Section: Results and Discussion Swelling Powermentioning
confidence: 88%
“…Reducing sugar are compounds with OH groups on their surfaces. These polar groups can form hydrogen bonds with water and retain them (Klang, et al, 2019). Total sugar is all sugar in the flour, not only The immersion time affects the total sugar content ( Figure 6) and reducing sugar ( Figure 7).…”
Section: Total Sugar and Reducing Sugarmentioning
confidence: 99%
“…The blanched tubers underwent the same process as described above. The flours obtained were packaged in polyethylene bags and stored in a desiccator to limit moisture exchange before its use for analysis [14].…”
Section: Production Of Blanched and Unblanched Irish Potato Floursmentioning
confidence: 99%
“…For this purpose, several treatments are applied, including bleaching [12]. Nevertheless, although effective, the water blanching process results in profound changes in the texture, organoleptic, chemical and even functional properties of the food [13,14]. In view of the above, it can be seen that these authors were interested in studying the nutritional value of Irish potato and neglecting the effect of bleaching on the nutritional value of irish potatoes flours and the use of these flours in combination with amylase sources (germinated maize flours) to improve the energy density of gruels.…”
Section: Introductionmentioning
confidence: 99%